2005
DOI: 10.1111/j.1439-0450.2005.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

VP2‐segment Sequence Analysis of Some Isolates of Bluetongue Virus Recovered in the Mediterranean Basin During the 1998–2003 Outbreak

Abstract: The complete nucleotide sequences of the VP2 segments of bluetongue virus (BTV) isolates recovered from Italy, Greece and Israel, from 1998 to 2003, were determined. Phylogenetic analysis of these sequences, those from related viruses and the South African vaccine strains, were used to determine the probable geographic origin of BTV incursions into Italy. Results indicated that viruses from each of the four serotypes isolated in Italy (2, 4, 9 and 16) possibly had a different origin. Analysis of the bluetongue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…This means that wind-borne spread of the infected vector from Israel to Rhodes is a likely route of introduction. It follows, from Savini et al (2004) and Potgieter et al (2005), that the BTV-16 strain found in Italy is indistinguishable from the live attenuated vaccine used in Israel (100% homology). Nomikou et al (unpublished data) showed that, based on segment 3/VP3, all the BTV-16 strains found in Greece, Turkey, Italy, Cyprus, Israel, Indonesia, India and Australia have a common Eastern origin, while BTV16 from Nigeria and Zimbabwe have an Western origin.…”
Section: Btv-16 Outbreak In Greecementioning
confidence: 99%
“…This means that wind-borne spread of the infected vector from Israel to Rhodes is a likely route of introduction. It follows, from Savini et al (2004) and Potgieter et al (2005), that the BTV-16 strain found in Italy is indistinguishable from the live attenuated vaccine used in Israel (100% homology). Nomikou et al (unpublished data) showed that, based on segment 3/VP3, all the BTV-16 strains found in Greece, Turkey, Italy, Cyprus, Israel, Indonesia, India and Australia have a common Eastern origin, while BTV16 from Nigeria and Zimbabwe have an Western origin.…”
Section: Btv-16 Outbreak In Greecementioning
confidence: 99%
“…Origin and movement of BTV strains and serotypes can be predicted by comparison of nucleotide sequences of virus isolates (Pritchard and Gould, 1995; Mellor and Wittmann, 2002; Mecham and Johnson, 2005; Mellor et al., 2008; Maan et al., 2009, 2010). Whereas VP2 sequences can be used to determine evolution of BTV within an endemic area as well as to predict movement of virus from one place to another (Mecham and Johnson, 2005; Potgieter et al., 2005; Maan et al., 2010), sequence data of other segments can predict both movement and reassortment (Mecham and Johnson, 2005; Batten et al., 2008). The sudden increase in virus activity and seriousness of the outbreaks recently in Andhra Pradesh led to the suspicion that new serotypes may have entered the country.…”
Section: Introductionmentioning
confidence: 99%
“…which of the 10 gene segments or combinations thereof are involved) for either BTV-8, MLV vaccine strains or laboratory adapted strains. Since strains of BTV readily exchange (reassort) gene segments during mixed infections of either animals or insects with more than one virus strain/serotype (Samal et al, 1987a, b;Stott et al, 1987;Cowley and Gorman, 1989;Mertens et al, 1989;Ramig et al, 1989;Pierce et al, 1998;Potgieter et al, 2005;Batten et al, 2008;Saegerman et al, 2009), there is a possibility that reassortment in the field will lead to the emergence of novel virus strains of serotypes other than BTV-8 with new features (e.g. the ability to cross the placenta and/or to cause disease in cattle).…”
Section: Transplacental Transmission and Infections Detected In Newbomentioning
confidence: 99%